Bile cast nephropathy is a common pathologic finding for kidney injury associated with severe liver dysfunction - van Slambrouck, Charles M.; Salem, Fadi; Meehan, Shane M.; Chang, Anthony (Kidney international, 2013)
Cholemic nephrosis represents a spectrum of renal injury from proximal tubulopathy to intrarenal bile cast formation found in patients with severe liver dysfunction. However, the contribution of this diagnosis has been largely forgotten in the modern literature. To more precisely define this, we conducted a clinicopathologic study of 44 subjects (41 autopsies and 3 renal biopsies) from jaundiced patients at the University of Chicago. Of these, 24 patients had bile casts with involvement of distal nephron segments in 18 mild cases and extension to proximal tubules for 6 severe cases. Eleven of 13 patients with hepatorenal syndrome and all 10 with cirrhosis (due to alcoholism) had tubular bile casts. These casts significantly correlated with higher serum total and direct bilirubin levels, and a trend toward higher serum creatinine, AST, and ALT levels. Bile casts may contribute to the kidney injury of severely jaundiced patients by direct bile and bilirubin toxicity, and tubular obstruction. Both mechanisms are analogous to the injury by myeloma or myoglobin casts. Accounting for the presence of renal bile casts provides a more complete representation of the renal injury that can occur in this unique clinical setting. Thus, bile cast nephropathy is an appropriate term for the severe form of injury observed in the spectrum of cholemic nephrosis. Additional studies are needed to establish the significance of this parameter for patient management in different clinical settings.